Synthesis, Characterization, and Antimicrobial Activity of a Novel Trisazo Dye from 3-Amino-4H-thieno[3, 4-c][1]benzopyran-4-one. (1st February 2018) - Tsemeugne, Joseph; Sopbué Fondjo, Emmanuel; Tamokou, Jean-de-Dieu; Rohand, Taoufik; Ngongang, Arnaud Djintchui; Kuiate, Jules Roger; Sondengam, Beibam Luc
Abstract : A new trisazo dye has been synthesized by coupling the diazonium ion of 3-amino-4H thieno[3, 4-c][1]benzopyran-4-one with 2- tert -butyl-4-methoxyphenol. The newly prepared trisazo dye was characterized by its physical, elemental, and spectroscopic data. 2D-NMR (COSY, HSQC, and HMBC) techniques were used to secure the structural assignments. The new trisazo dye (compound7 ) along with precursors3, 4, and6 was screened by microdilution susceptibility assay for antibacterial and antifungal activities towards eight bacterial strains and three yeasts selected on the basis of their relevance as human pathogens. The results showed that compound7 (MIC = 2–128  μ g/mL) was the most active as compared with its precursors. The most resistant microorganisms were V. cholerae NB2 and V. cholerae SG24, whereas the most sensitive microorganism was C. neoformans. The overall results of this study indicated that compound7 had the greatest potential value against both yeasts and multidrug-resistant bacteria, so further investigation is warranted.